How Board Size and Board Independence Affect Insurance Companies’ Performance - Andromahi KUFO; Eriona SHTEMBARI (European Journal of Interdisciplinary Studies)
In the last two decades, corporate governance has had its “shining era of research”, especially in developed countries, where good management, transparency, and reaching the investors’ basis meant a huge deal for big corporations. Without reducing the importance of the subject, such issues have reached the developing countries a bit later in time, and investigation on the matter has been not so extensive, especially due to the lack of proper legal framework and real data. Yet corporate governance is reaching an interest lately in emerging markets, like Albania which aspires to be in the Union, and due to the “new normality” in the management style, which requires a re-adjustment of business structures. This paper attempts to determine the role that board size and board independence as corporate governance variables have in a company’s performance, measured by the board of directors’ characteristics. Even though at a very initial stage of its development, the insurance industry in Albania has applied certain corporate governance structures, mainly because insurance companies are part of international groups. As the insurance industry is integrated into the wider financial services and nowadays is getting more important in the local service-based financial market, understanding the factors affecting its profitability becomes important too. The results of this study show that there is a negative relationship between board size and corporate performance, while there is a positive relationship between board independence and corporate performance.